Отметь как лутшый pls
Пошаговое объяснение:
693÷23 = 30.(1304347826086956521739)
- 6 9 3 2 3
6 9 3 0 . 1 3 0 4 3 4 7 8 2 6 0 8 6 9 5 6 5 2 1 7 3 9 23 × 3 = 69
- 3 0 69 - 69 = 0
2 3 23 × 1 = 23
- 7 0 30 - 23 = 7
6 9 23 × 3 = 69
- 1 0 0 70 - 69 = 1
9 2 23 × 4 = 92
- 8 0 100 - 92 = 8
6 9 23 × 3 = 69
- 1 1 0 80 - 69 = 11
9 2 23 × 4 = 92
- 1 8 0 110 - 92 = 18
1 6 1 23 × 7 = 161
- 1 9 0 180 - 161 = 19
1 8 4 23 × 8 = 184
- 6 0 190 - 184 = 6
4 6 23 × 2 = 46
- 1 4 0 60 - 46 = 14
1 3 8 23 × 6 = 138
- 2 0 0 140 - 138 = 2
1 8 4 23 × 8 = 184
- 1 6 0 200 - 184 = 16
1 3 8 23 × 6 = 138
- 2 2 0 160 - 138 = 22
2 0 7 23 × 9 = 207
- 1 3 0 220 - 207 = 13
1 1 5 23 × 5 = 115
- 1 5 0 130 - 115 = 15
1 3 8 23 × 6 = 138
- 1 2 0 150 - 138 = 12
1 1 5 23 × 5 = 115
- 5 0 120 - 115 = 5
4 6 23 × 2 = 46
- 4 0 50 - 46 = 4
2 3 23 × 1 = 23
- 1 7 0 40 - 23 = 17
1 6 1 23 × 7 = 161
- 9 0 170 - 161 = 9
6 9 23 × 3 = 69
- 2 1 0 90 - 69 = 21
2 0 7 23 × 9 = 207
3 210 - 207 = 3
Отметь как лутшый pls
Пошаговое объяснение:
693÷23 = 30.(1304347826086956521739)
- 6 9 3 2 3
6 9 3 0 . 1 3 0 4 3 4 7 8 2 6 0 8 6 9 5 6 5 2 1 7 3 9 23 × 3 = 69
- 3 0 69 - 69 = 0
2 3 23 × 1 = 23
- 7 0 30 - 23 = 7
6 9 23 × 3 = 69
- 1 0 0 70 - 69 = 1
9 2 23 × 4 = 92
- 8 0 100 - 92 = 8
6 9 23 × 3 = 69
- 1 1 0 80 - 69 = 11
9 2 23 × 4 = 92
- 1 8 0 110 - 92 = 18
1 6 1 23 × 7 = 161
- 1 9 0 180 - 161 = 19
1 8 4 23 × 8 = 184
- 6 0 190 - 184 = 6
4 6 23 × 2 = 46
- 1 4 0 60 - 46 = 14
1 3 8 23 × 6 = 138
- 2 0 0 140 - 138 = 2
1 8 4 23 × 8 = 184
- 1 6 0 200 - 184 = 16
1 3 8 23 × 6 = 138
- 2 2 0 160 - 138 = 22
2 0 7 23 × 9 = 207
- 1 3 0 220 - 207 = 13
1 1 5 23 × 5 = 115
- 1 5 0 130 - 115 = 15
1 3 8 23 × 6 = 138
- 1 2 0 150 - 138 = 12
1 1 5 23 × 5 = 115
- 5 0 120 - 115 = 5
4 6 23 × 2 = 46
- 4 0 50 - 46 = 4
2 3 23 × 1 = 23
- 1 7 0 40 - 23 = 17
1 6 1 23 × 7 = 161
- 9 0 170 - 161 = 9
6 9 23 × 3 = 69
- 2 1 0 90 - 69 = 21
2 0 7 23 × 9 = 207
3 210 - 207 = 3
7x-20x=16-42
-13x=-26
x=2
б) 1,5x+12=-3
1,5x=-3-12
1,5x=-15
x=-10
в)1/6x+9/6=-1/3x
1/6x+1/3x=-9/6
1/2x=-9/6
x=-3
г)3/4x+6=2x+1
3/4x-2x=1-6
3/4x-2x=-5
-5/4x=-5
x=4